Application of Rasch analysis to Turkish version of ECOS-16 questionnaire. - (:unkn) unknown (My University, 2014)
The aim of this study is to reevaluate validity of Turkish version of the ECOS-16 questionnaire by using Rasch analysis in post-menopausal women with osteoporosis. ECOS-16 (Assessment of health related quality of life in osteoporosis) is a quality of life questionnaire, which is convenient for measuring the quality of life of post-menopausal women with osteoporosis. 132 post-menopausal women with osteoporosis who attended Uludag Universtity, Atatürk Rehabilitation and Research Center between January 2010 and March 2011 were included in this study. The subjects filled out Turkish version of ECOS-16 questionnaire by themselves. The Rasch model was used for assessing construct validity of ECOS-16 data. Internal consistency was assessed by Cronbach's alpha coefficient. The mean infit and outfit mean square (z std) were found as 1.08 (0.1) and 1.02 (-0.1), respectively. The separation indices for the item and person were found as 7.72 and 3.13; the separation reliabilities were 0.98 and 0.91, respectively. Cronbach's alpha coefficient was found as 0.90. The construct validity of ECOS-16 questionnaire was assessed by Rasch analysis.